Revisiting Roel Meijer's Typology of Salafism: A Critical Reading of the Salafi Movement Studies - Azzam Musoffa (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2025)
This research aims to review the typology of Salafists introduced by Roel Meijer in his work "The Global Salafism" to understand the core of Salafi thought, including fragmentation within Salafists and apply it in the latest context in Indonesia. To explore this object, the researcher utilized library research by presenting several perspectives outside Roel Meijer's work, both from Western scholars and Muslims who discussed the main ideology of Salafis. The literature studies showed several misconceptions about Salafi's original thought by both Western and Muslim scholars. The misconceptions understood by Western scholars tend to attribute reform movements such as Jamaluddin Al-Afghani or Muhammad Abduh to Salafis. As for the misconceptions understood by Muslims themselves, who are at odds with the main ideas of Muhammad bin Abdul Wahab, they radicalize the output of their thoughts so that it causes acts of violence that cross the threshold of humanitarian tolerance in the present era. Some of the misconceptions by internal Salafis included excessive understanding of the concept of Al-Walaa' wal Baraa', excessive hatred of the Shi'a, and the application of the concept of amr ma'ruf nahy munkar, which is restrictive, especially because it used backup from the government. The results suggested the typology of Salafism to be divided into only two, based on the same condition as those two groups, the rejection of using only logical thinking without Qur’anic or hadith basis, namely, Purists and Jihadis.